1999
DOI: 10.1093/chemse/24.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia as an Attractive Component of Host Odour for the Yellow Fever Mosquito, Aedes aegypti

Abstract: Behavioural responses of Aedes aegypti mosquitoes to ammonia were investigated in a modified Y-tube olfactometer. Ammonia was attractive in concentrations from 17 ppb to 17 ppm in air when presented together with lactic acid. Aqueous solutions of ammonia salts in concentrations comparable to those found in human sweat also increased the attractiveness of lactic acid. The role of lactic acid as an essential synergist for ammonia became further apparent by the fact that ammonia alone or in combination with carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
113
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 20 publications
8
113
0
4
Order By: Relevance
“…Displacements of the ticks were sampled every 0.2 s and a running mean over five vectors was applied at 40 s intervals for graphical representation. Note the increased walking speed in the presence of breath (observed in half of the ticks presented with this stimulus), the contrastingly lower speed in response to acetone and NO, and the unchanged speed in the presence of CO 2 may be that presentation of NH 3 with other chemicals is necessary in order to elicit a behavioural response in A. variegatum, as shown by Geier et al (1999) for mosquitoes.…”
Section: Discussionmentioning
confidence: 81%
“…Displacements of the ticks were sampled every 0.2 s and a running mean over five vectors was applied at 40 s intervals for graphical representation. Note the increased walking speed in the presence of breath (observed in half of the ticks presented with this stimulus), the contrastingly lower speed in response to acetone and NO, and the unchanged speed in the presence of CO 2 may be that presentation of NH 3 with other chemicals is necessary in order to elicit a behavioural response in A. variegatum, as shown by Geier et al (1999) for mosquitoes.…”
Section: Discussionmentioning
confidence: 81%
“…The BGL contains substances that are found on human skin, such as ammonia, lactic acid and caproic acid that also attracts for host seeking females Ae. aegypti (Geier et al 1999, Bosch et al 2000.…”
mentioning
confidence: 99%
“…This factor is important, not just in increasing the chances of survival, but also in guaranteeing the emergence of a large number of adults. 3,5 Geier et al 15 (1999) showed in a laboratory, that ammonium nitrate is a chemical component which attracts the Aedes aegypti mosquito to their host. That females are attracted to nitrogenous compounds, was also verifi ed by Sunish et al 19 (2003) in egg laying by the Japanese encephalitis vector Culex tritaeniorhynchus.…”
mentioning
confidence: 99%